ASSESSING THE EFFECTIVENESS OF GAME-BASED LEARNING FOR ENGLISH VOCABULARY DEVELOPMENT USING LUDO PEDAGOGY - Muhammad Najih Al Azizi; Nina Sofiana (Universitas Wiralodra, 2025)
Vocabulary acquisition is crucial for young learners as it forms the foundation for communication skills. However, traditional vocabulary instruction often lacks engagement, leading to low retention and motivation. This study investigates the effectiveness of game-based learning, particularly Ludo pedagogy, in enhancing English vocabulary among fourth-grade students at an elementary school in Jepara. Using a pre-experimental one-group pretest-posttest design, 24 students participated in four treatment sessions. Data collection included pretests and posttests to assess vocabulary improvement. The findings revealed a statistically significant increase, with an average gain of 9.94 points. A dependent t-test confirmed that game-based learning positively impacted vocabulary retention and engagement. The integration of structured board games with instructional flashcards created an interactive learning environment that enhanced student participation. This study contributes to game-based education by demonstrating its potential to improve vocabulary acquisition. The results suggest that incorporating game-based strategies can effectively support vocabulary learning, making it more enjoyable and meaningful for young learners. Future research should explore its long-term effects and broader applications in various educational settings to further evaluate its instructional potential.